Res Publica : Plato's republic in classical German philosophy - Zöller, Günter, 1954- (Tang Chun-I lecture series., 2015)
"In Res Publica, Günter Zöller offers a concise and perceptive analysis of the influence that Plato's Republic had on the political thought of three leading German philosophers rarely discussed together -- Kant, Hegel, and Fichte. He investigates how these three thinkers engaged with one of the founding texts of Western political philosophy to offer their particular interpretations of the forms and norms of the political organization known as the "commonwealth" or res publica. Professor Zöller contextualizes the encounter between an ancient thinker and his modern descendants to demonstrate how the ongoing dialogue between ancient republican thought and nineteenth-century German Idealism extends to the modern era."--Publisher's website.